MODERN APPROACHYeS TO TEACHING STUDENTS THROUGH INDEPENDENT STUDY AT A HIGHER EDUCATIONAL INSTITUTION (Scientific journal of the Fergana State University, 2024)
The main goal of this article is to clarify the didactic aspects of students' activities in the independent education process in higher educational institutions. In particular, pedagogical possibilities of independent education of students of higher educational institutions were analyzed from a scientific and theoretical point of view. Scientific-methodological literature on the situation of organizing students' independent activities was analyzed and author's approaches to a number of tasks, modern approaches and solutions to the problem were proposed. Also, the main didactic tasks of improving the independent work system and the scientific-theoretical features of their implementation were studied and recommended.Changes in the education system are closely related to the content of education. Updates also require thinking about new forms and methods of organizing student learning. In this sense, the organization of students' independent work is not only an important form, but also an important part of the educational process. All this involves acquiring modern methods of teaching (receiving), developing students' creative abilities, taking into account the opportunities and potential of each student, moving from group studies to individual studies. The problem of forming pedagogical foundations of students' independent work is relevant for all types of education.The main goal of this article is to clarify the didactic aspects of students' activities in the independent education process in higher educational institutions. In particular, pedagogical possibilities of independent education of students of higher educational institutions were analyzed from a scientific and theoretical point of view. Scientific-methodological literature on the situation of organizing students' independent activities was analyzed and author's approaches to a number of tasks, modern approaches and solutions to the problem were proposed. Also, the main didactic tasks of improving the independent work system and the scientific-theoretical features of their implementation were studied and recommended.Changes in the education system are closely related to the content of education. Updates also require thinking about new forms and methods of organizing student learning. In this sense, the organization of students' independent work is not only an important form, but also an important part of the educational process. All this involves acquiring modern methods of teaching (receiving), developing students' creative abilities, taking into account the opportunities and potential of each student, moving from group studies to individual studies. The problem of forming pedagogical foundations of students' independent work is relevant for all types of education.